Visi Moderat Islam - Ahmad Luthfi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Why did the early religion of its potential be a clue to God turn out to be fragmented in a binnary opposition matrix? From this anxiety the author focuses on the Binnary Opposition, which derives two sub-formulations of the problem. First, how to unravel the perspective of binnary opposition, which became the root of religious primordiality? Second, how to put the future religious perspective in interdependent position ?. What is the purpose of the speaker, from the first sub-formulation of the problem, is to explore the process of establishing a binnary opposition perspective in religion, while the second sub-formulation of the problem is to formulate a future religious perplexity in harmony with the moderate vision of Islam. to review the problem formulation we use the Interrelegious studies approach by utilizing cosmothreandic theory of Raymond pannikar. From this approach it is concluded from the formulation of the first problem, that the Islamic discourse which moves on the level of binnary opposition on its essential is Islam in the logos matrix. This matrix necessitates categories such as Substantial Islam and formalists. With this comes the tension between one another. While from the formulation of the second problem, to go to the moderate vision of Islam needs to replace the perspective of Islam that leads to interdependent position. In this sphere Islam is no longer relying on the analysis of binnary opposition but on the vision of justice and humanity.